Economic-Environmental-Energetic (3E) analysis of Photovoltaic Solar Energy Systems: Case Study of Mechanical & Renewable Energy Engineering Departments at Wadi AlShatti University - Amer, Khaled; Irhouma, Mukhtar; Hamdan, Mohammed; Aqila, Abdulhafiz; Ahmed, Alsanossi; Fakher, Masoud; Alkhazmi, Ali (Wadi Alshatti University Journal of Pure and Applied Sciences, 2025)
This research aims to prove the technical, economic and environmental feasibility of a PV solar energy system to cover the basic electrical load in an academic institutional building - the Departments of Mechanical and Renewable Energy Engineering at Wadi Alshatti University, Libya. The present research comes in line with the aspirations of the Libyan state to shift towards renewable and clean energies in compliance with the Paris Climate Change Treaty, and also in line with the university’s mission to achieve sustainability and preserve the environment in the local community. The present study discussed the economic, environmental and energy impacts of the PV solar system size by estimating the energy costs (LCOE), the power supply reliability (PSR), the amount of load that can be covered using solar energy, and the extent of the system’s success in alleviating the carbon footprint on society by calculating the social cost and the amount of CO2 that was prevented from emission to the atmosphere.